Coal industrial supply chain network: Mongolian capabilities across the Asian market - Purev, Bolortuya; He, Weida (Technium Social Sciences Journal, 2021)
World Coal market experiences rapid changes nowadays: phasing out coal and switching to gas and renewables source of primary energy. Countries of Asia are also pursuing strategies of sustainable environmental development and seeking for new sources of energies. But energy transition will not occur in several years, this transition requires decades of investment and technology development. Up to that time coal will remain main source of energy, especially for China and other South-Eastern Asian countries. Mongolia is a landlocked country with high dependence from mining sector and this trend will likely to continue for at least a decade to diversify economy. Since that time, Mongolia needs to reidentify its strategies for fast changing Asian market. Major concern of domestic coal sector is to benefit from coal export and determine opportunities for coal sector development. This study will be a reliable source for policymakers and coal exporters.